2018
DOI: 10.1093/mnras/sty2031
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of the thermal Sunyaev–Zeldovich effect and 2MASS galaxies: probing gas physics in the local Universe and beyond

Abstract: We present a first joint analysis of the power spectra of the thermal Sunyaev-Zeldovich (tSZ) effect measured by the Planck and the number density fluctuations of galaxies in the 2MASS redshift survey (2MRS) catalog, including their cross-correlation. Combining these measurements with the cosmic microwave background (CMB) data and CMB lensing of Planck assuming a flat ΛCDM model, we constrain the mass bias parameter asthe Planck cluster mass should be 35% lower than the true mass. The mass bias determined by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 58 publications
9
79
0
Order By: Relevance
“…(3) for the reason described in Section 3.1. 4 This constraint is different from that shown in Makiya et al (2018) due to the difference of dark matter mass function, the tSZ auto-power spectrum data and the treatment of the non-Gaussian term of the covariance matrix, as noted in Section 2 and 3. have found that the mass bias of Planck clusters is constrained to be B = 1.37 ± 0.20 or (1 − b) = B −1 = 0.73 ± 0.11 (68% C.L.) for σ8 < 0.9.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…(3) for the reason described in Section 3.1. 4 This constraint is different from that shown in Makiya et al (2018) due to the difference of dark matter mass function, the tSZ auto-power spectrum data and the treatment of the non-Gaussian term of the covariance matrix, as noted in Section 2 and 3. have found that the mass bias of Planck clusters is constrained to be B = 1.37 ± 0.20 or (1 − b) = B −1 = 0.73 ± 0.11 (68% C.L.) for σ8 < 0.9.…”
Section: Resultsmentioning
confidence: 95%
“…The Gaussian term of the covariance matrix is taken from Table 3 of Bolliet et al (2018). In Makiya et al (2018) we calculated the non-Gaussian term at each step of parameter inference. However Carron (2013) pointed out that such a parameter-dependent covariance matrix adds extra artificial information and can bias the parameter constraints.…”
Section: Likelihood Analysismentioning
confidence: 99%
“…surements. Although the signal of tSZ auto-power spectrum comes from galaxy clusters and groups with a wide range of mass (see, e.g., Makiya et al 2018), mass calibration measurements probe only into massive clusters. The tSZ-WL cross-correlation is sensitive to the structures at lower redshifts compared to the tSZ auto-power spectrum (Battaglia et al 2015).…”
Section: Comparison With Mass Calibration Measurementsmentioning
confidence: 99%
“…However, future CMB mission concepts such as CORE (Delabrouille et al 2018;Remazeilles et al 2018) and PICO could take a dramatic leap forward in sensitivity and spectral coverage versus that of Planck, enabling an increase in the number of detected SZ clusters to a few × 10 5 (Melin et al 2018b). This will open the way for detailed SZ studies with unprecedented precision, allow a vast number of cross-correlation studies, and provide additional constraints on cosmological parameters and neutrino mass and number (e.g., see Hill & Pajer 2013;Bolliet et al 2018;Makiya et al 2018;Salvati et al 2018;The Simons Observatory Collaboration et al 2018).…”
Section: Future Space Missionsmentioning
confidence: 99%